Le plaisir des langues s’apprend sur scène - Theresa Heyer (Recherches)
This article reports on the experience of two different ARTLINGO workshops: one, in which students staged a play in German, and the other, in which poems from different languages were translated. In both workshops, intensive reading, writing and translation work was followed by a performance of the texts worked on. The key to the success of these projects was to create group cohesion and eliminate the fear of being judged for speaking a foreign language. What’s more, they were opportunities to get to know and appropriate the (inter)cultural treasures of another culture.